A highly sensitive electrochemical biosensor based on AuNP-modified gold electrodes for selective determination of serum levels of crosslaps - Khashayar, Patricia (3 Biotech, 2017)
This article explains a step-wise protocol to develop an electrochemical sensor to quantify serum levels of C-telopeptide (CTX) crosslinks also known as crosslaps in a matter of minutes and with high level of accuracy. The technique needs only one-step (incubation) and can thus be used for point of care screening. Due to the excellent electrical properties of the as-prepared immunosensor, CTX levels were successfully measured from 1 to 1000 pg/mL. This is while the normal reference of the marker is 50–450 pg/mL, suggesting that the sensor can acceptably detect CTX. The results also showed a good correlation with ECLIA in measuring serum levels of CTX.